A review of greenhouse gas emissions from selected wetlands in the Vietnamese Mekong Delta - Farmer, J.; Ghosh, Surajit; Rajakaruna, Punsisi; Holmatov, Bunyod (International Water Management Institute (IWMI). CGIAR Initiative on Low-Emission Food Systems, 2023)
Nearly half of Vietnam’s wetlands are concentrated in the Vietnamese Mekong Delta. Wetlands play an important role in carbon storage while contributing to Vietnam’s biological diversity and economy. This report reviews the wider literature to understand how land use within the Vietnamese Mekong Delta and likely management scenarios can impact greenhouse gas emissions. The report is structured into six main sections covering an introduction, key characteristics of the Vietnamese Mekong Delta wetlands, literature-based greenhouse gas emissions assessments, a review of commonly available models for estimating greenhouse gas emissions, estimations of emissions using a select number of reviewed models, with a focus on paddy rice, and finally ends with some conclusions.